(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
The Soviet government has taken great steps to restructure the education system in the Uzbek USR. The education system was largely rebuilt during the Cultural Revolution. But the main goal of the Soviets during this period is the training of personnel who will serve the party. This article provides some information about how the Soviet government implemented its ideas in teaching history in schools.